CSR COMMUNICATION PT PERTAMINA IN LAND UTILIZATION HOME GARDENS AND THE ENVIRONMENT BABUL ULUM ISLAMIC BOARDING SCHOOL - Pipit Anggaeni; Desy Misnawati; Moh. Hafizni (Jurnal Scientia, 2023)
The purpose of this research is to understand PT Pertamina's CSR Communication in the utilization of home gardens and the environment of the Babul Ulum Islamic Boarding School. Theoretical analysis uses the theory of innovation diffusion and community participation. The research method uses descriptive qualitative. Data collection is done through interviews, observation, and documentation. The results showed that the process of diffusion of innovation in "PT Pertamina CSR Extension Communication in Utilizing Community Home Gardens" involved the identification and communication of new ideas about the utilization of home gardens by PT Pertamina to the Mariana community. Through counseling, training, and open communication, the Mariana community accepted and understood this innovation. Some individuals and groups began to adopt the practice and shared their positive experiences with the rest of the community, which triggered further adoption. This process demonstrates how effective communication and community participation play an important role in the successful diffusion of innovations.